2010
DOI: 10.1007/s11103-010-9620-9
|View full text |Cite
|
Sign up to set email alerts
|

Light and temperature sensing and signaling in induction of bud dormancy in woody plants

Abstract: In woody species cycling between growth and dormancy must be precisely synchronized with the seasonal climatic variations. Cessation of apical growth, resulting from exposure to short photoperiod (SD) and altered light quality, is gating the chain of events resulting in bud dormancy and cold hardiness. The relative importance of these light parameters, sensed by phytochromes and possibly a blue light receptor, varies with latitude. Early in SD, changes in expression of light signaling components dominate. In P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
141
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(151 citation statements)
references
References 95 publications
7
141
0
3
Order By: Relevance
“…Several authors reported that temperature, water and nutrient availability play important roles in the induction of shoot growth cessation (Koundouras et al, 1999;Leeuwen et al, 2004;Coipel et al, 2006). In addition, photoperiod (Wake & Fennell, 2000;Heide, 2008;Garris et al, 2009;Victor et al, 2010) and probably thermoperiod (Olsen, 2010;Tanino et al, 2010) also play important roles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several authors reported that temperature, water and nutrient availability play important roles in the induction of shoot growth cessation (Koundouras et al, 1999;Leeuwen et al, 2004;Coipel et al, 2006). In addition, photoperiod (Wake & Fennell, 2000;Heide, 2008;Garris et al, 2009;Victor et al, 2010) and probably thermoperiod (Olsen, 2010;Tanino et al, 2010) also play important roles.…”
Section: Resultsmentioning
confidence: 99%
“…The vegetative growth phase is dependent on several factors, and meteorological variables have an essential role in the control of grapevine development (Pouget, 1972;Andreini et al, 2009;Garris et al, 2009;Olsen, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most flowering plants use photoperiod and temperature variations to detect seasonal shifts and reproductive periods (Boss and others 2004;Jaeger and others 2006;Penfield 2008;Adrian and others 2009;Amasino 2010;Olsen 2010). Vernalization and bud dormancy are two distinct mechanisms that allow temperature changes to affect flowering time (Chouard 1960;Penfield 2008).…”
Section: Introductionmentioning
confidence: 99%